Pengaruh Model PBP Terhadap Kemampuan Membuat Media Pembelajaran Sederhana Mahasiswa PGSD - M, Sulkipli; Maryam, Andi; Mardiah, Ainun; Musa'ad, Faida (Educatio, 2025)
The study seeks to assess the impact of project-based learning on the ability of Pre-Service Elementary School Teachers (PGSD) at Muhammadiyah University of Sorong to design simple learning media. A pre-experimental one-group pretest-posttest design was employed, and the results showed a significant improvement in students' cognitive abilities after participating in project-based learning. Additionally, psychomotor assessments demonstrated highly commendable outcomes, with average scores surpassing the good criteria. Statistical analysis using the Paired Sample T-Test confirmed a statistically significant difference between pre-test and post-test scores (p < 0.05). These findings imply that project-based learning is an effective pedagogical approach for developing students' competencies in designing simple learning media, especially in regions with limited educational resources like Papua. Kata kunci: Simple Learning Media, PGSD Students, Project-Based Learning